Upconversion nanoparticle bioconjugates characterized by capillary electrophoresis. Issue 17 (1st July 2018) - Vaneckova, Tereza; Smerkova, Kristyna; Zitka, Jan; Hynek, David; Zitka, Ondrej; Hlavacek, Antonin; Foret, Frantisek; Adam, Vojtech; Vaculovicova, Marketa
Abstract: Upconversion nanoparticles (UCNPs) are an emerging class of optical materials with high potential in bioimaging due to practically no background signal and high penetration depth. Their excellent optical properties and easy surface functionalization make them perfect for conjugation with targeting ligands. In this work, capillary electrophoretic (CE) method with laser‐induced fluorescence detection was used to investigate the behavior of carboxyl‐silica‐coated UCNPs. Folic acid, targeting folate receptor overexpressed by wide variety of cancer cells, was used for illustrative purposes and assessed by CE under optimized conditions. Peptide‐mediated bioconjugation of antibodies to UCNPs was also investigated. Despite the numerous advantages of CE, this is the first time that CE was employed for characterization of UCNPs and their bioconjugates. The separation conditions were optimized including the background electrolyte concentration and pH. The optimized electrolyte was 20 mM borate buffer with pH 8.